Hypertension attenuates the prognostic value of coronary artery calcification scoring in low-risk patients. Issue 12 (27th October 2020) - Maclean, Edd; Sehmi, Joban; Kanaganayagam, Gajen; Nicol, Edward David
Abstract : Objectives: In outpatients with suspected ischaemic symptoms, we investigated the impact of risk factor profile on the prognostic value of coronary artery calcium scoring (CACS) and CT coronary angiography (CTCA). Methods: 772 consecutive patients underwent CACS and CTCA; 52 patients (6.7%) with significant coronary artery lesions underwent revascularisation within 60 days and were excluded. 720 remaining patients were followed up for 38.1±17.4 months. Results: Late presentation (after 60 days) major adverse cardiovascular events (MACEs) were recorded in 27 patients (3.8%). Hypertension was strongly associated with adverse outcomes (unadjusted HR 6.5 (2.9 to 14), p<0.001), and hypertensive patients had double the prevalence of non-calcified plaque versus normotensive individuals (30.2% vs 14.3%, p<0.001). Adjusting for confounders, severe stenosis at CTCA was predictive of MACE for normotensive and hypertensive patients (HR 9.6 (2.8 to 43.1), p<0.001, and HR 6.2 (2.4 to 16.1), p<0.001, respectively). CACS alone was not predictive of MACE throughout the cohort (HR 1.001 (0.9997 to 1.001), p=0.36) and when adjusting for confounders, a cut-off of CACS>400 predicted MACE in normotensive individuals (HR 10.6 (2.41 to 49.3), p<0.001) but not in hypertensive individuals (HR 1.3 (0.5 to 3.6), p=0.56). Zero calcium score did not mitigate the risk of MACE (HR 0.84 (0.39 to 1.8), p=0.65) and 13/27 patients (48.1%) who suffered MACE had a 0 calcium score; all had hypertension. Conclusions: In low-risk patients with stable cardiovascular symptoms, CTCA provides important additive prognostic information over CACS, and CACS (including CACS>400) underestimated cardiovascular risk in patients with hypertension. This may relate to the increased prevalence of non-calcified plaque in these individuals.